Shevelya V.V., Kupiec B., Kalda G.S., Sokolan J.S. Changing of tribological and rheological properties in the process of repeatedly-cycling friction considering baushinger’s effect. - Шевеля, В.В.; Купец, Б.; Калда, Г.С.; Соколан, Ю.С. (Problems of Tribology, 2017)
When evaluating the effectiveness of surface thermic strengthening of mild steel by electroarc treatment, the changes of sclerometric indices and acoustic-emission activity of friction zone under conditions of repeatedly-monodirectional and cyclically reversed scratch testing as a result of contact load were studied. In the process of reversed friction, the tribologic analog of Baushinger’s effect was determined; the level of its occurrence depends on steel structure state, contact load, depth of controlled layer and quantity of frictional load.Key words: sclerometric testing, scratch-analysis, wear resistance, frictional force, acoustic emission, Baushinger’s effect, thermal strengthening, dislocations.